Analysis of Ease of Use, Quality of Service and Promotion on Interest in Buying Using E-Wallet - Fitria, Lailani; Khotimah, Khusnul; Yani, Ahmad; Rafki, Rafnelly; Oktarina, Yolanda; Nofriadi, Nofriadi (Dinasti International Journal of Digital Business Management, 2024)
This study aims to determine how much influence the variables of ease of use, service quality, and promotions have on consumer buying interest in making transactions using e-wallets. The method used is library research and qualitative description by examining various sources related to the research object. The results showed that as many as 876 respondents who used Shopeepay, OVO and Linkaja agreed in terms of ease of use, while 100 other respondents said that even if it is easy, it is not necessarily used. Furthermore, Gopay and Dana, with a total of 190 respondents, stated that there was a significant influence on the service quality variable. Followed by the promotion variable represented by all e-wallet users, with a total of 48 respondents saying that the majority of millennial users have no significant influence on purchase intention, but on the other hand, it has an influence on Gen Z. It can be concluded that the presence of an e-wallet has been widely used by the public in making transactions with various conveniences, quality and promotions provided, but in terms of usage, there are still many who have not explored the e-wallet, so it is hoped that this can be expanded further.